Ovicidal Activity of Berenuk (Crescentia cujete L.) Fruit Extract on the Hatchability of Aedes aegypti L. Eggs - Astreapuspita Vicanisa Armanda; Rahayu Sofia Ery; Setiowati Frida Kunti (BIO Web of Conferences, 2025)
Synthetic ovicide induces resistance eggs. Berenuk (Crescentia cujete L.) fruit contains secondary metabolites as ovicidal agents. This study aims to analyse the bioactive compounds in the fruit rind and flesh extracts of C. cujete using colour reagent methods, analyse the ovicidal activity of the extracts on the hatchability of Aedes aegypti L. eggs, and determine their effective concentration (LC50). This experimental study used a Randomized Block Design with 4 replications and was applied to 1000 of Ae. aegypti eggs. Extract concentrations respectively were 50, 100, 200, and 400 ppm. Data on unhatched eggs were analysed using two-way Anova, and a probit test was used to determine the LC50 value. The phytochemical screening result's presence of alkaloids, saponins, tannins and triterpenoids in both the extracts, while also flavonoids in the flesh. The higher concentration and longer application times, the greater inhibition of egg hatchability. After 120-hours, the fruit rind and flesh extracts significantly inhibited egg hatching by 64% and 77% at 400 ppm. The LC50 for each extract were 159.580 and 136.051 ppm at 96 hours, and 191.340 and 173.731 ppm at 120 hours after application. These outcomes show that C. cujete fruit extracts have the potential as botanical ovicides.